Christian Saluan: The Existence Of The Saluan “Monika” Life Cycle Ritual In The Gklb Betania Sinampangnyo Congregation - Yohanes Bandong (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2022)
The Saluan tribe is one of the tribes who inhabit the Banggai Regency, Central Sulawesi. The majority of this tribal community is Muslim and has a distinctive tribal language that is used in even daily rituals, namely the Saluan language. This article aims to see the existence of life cycle rituals carried out by the Saluan tribal community who are Christian. The life cycle ritual carried out by the Saluan Christian tribal community is realized through the traditional Saluan